Phytochemical Screening and Evaluation of in Vitro Anti-Inflammatory Activity of Ethanolic Extract of Terminalia Mantaly H. perrier Leaves Using BSA Protein Denaturation Assay - Harfan, Anita Anida; Mulyani, Reni; Mulyadi, Dikdik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The biological reaction to tissue damage known as inflammation is typified by the production of mediators including cytokines and prostaglandins. Long-term usage of non-steroidal anti-inflammatory medicines (NSAIDs) can have negative effects, despite their widespread use. This study explores the potential of Terminalia mantaly H. perrier (ketapang kencana), a plant known to contain various bioactive compounds, as a natural anti-inflammatory agent. The aim of this study was to analyze the phytochemical content and evaluate the anti-inflammatory activity of ethanol extracts of T. mantaly leaves using the Bovine Serum Albumin (BSA) protein denaturation method. 70% and 96% ethanol were used in the maceration process for extraction. The 70% ethanol extract included flavonoids, tannins, saponins, triterpenoids, terpenoids, and alkaloids, according to phytochemical screening. With an IC₅₀ value of 27,86 ppm Terminalia mantaly etanol extract 70%, the anti-inflammatory test revealed that the 70% ethanol extract at 400 ppm reduced protein denaturation by 92,29%, which was comparable to the inhibition by sodium diclofenac (84,04% at 50 ppm). These results suggest that polar compounds in the 70% ethanol extract significantly contribute to its anti-inflammatory effect. Therefore, T. mantaly leaf extract demonstrates promising potential as a natural phytopharmaceutical candidate for inflammation therapy.